Analysis Of Errors In The Formation Of Fi'il Mudari' By The University Of Malaysia Sarawak Students/ تحليل الأخطاء في صياغة الفعل المضارع لدى طلاب جامعة سراوك الماليزية - Kadai, Kazimah; Baharudin, Harun; Wicaksono, Triadi; Fitriani, Nisa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Arabic verbs are formed by adding components to indicate number, gender, and tense. The mastery of verb formation in the present tense (fi'il muḍāri') is still weak among students. This study aims to identify the types of errors in forming fi'il muḍāri' and to analyze the factors that lead to these errors. This study is qualitative in nature, using a content analysis design. Data was collected through document analysis by examining 108 scripts of final exam answers from students enrolled in the Arabic Language Level 1 course (PBU1133) at the Faculty of Education, Language, and Communication, UNIMAS. The data was analyzed using a descriptive and thematic approach assisted by NVivo software. The study found that students made several errors in forming fi'il muḍāri'. The factors contributing to these errors are that students are confused about the various Arabic grammar methods, have poor mastery of the aspects of Arabic orthography, and lack proficiency in the rules for forming the fi'il muḍāri'. The results of this study can serve as a guide in teaching and learning sessions to ensure that types of errors in the formation of fi'il muḍāri' can be avoided by placing special emphasis on the factors that contribute to these errors.